The effect of shock absorbing sports surfaces in jumping - Dura, J. V.; Hoyos, J. V.; Lozano, L.; Martinez, A. (Sports Engineering, 1999)
A jumping movement was performed over five different sports surfaces within a wide range of shock absorbency. The sports surfaces tested had an influence in performance and in the accelerations measured on human subjects. The subjects tested changed their movements and adaptation to the surface was observed. The surfaces with high shock absorbency (more than 70%) did not improve protection significantly and reduced performance in the jumping movement.